Student Satisfaction Analysis of Siater Using End User Computing Statisfaction (EUCS) - Erlangga ERLANGGA; Jefri Krisna Putra (Bandar Lampung University (UBL), 2014)
The purpose of this research is to know the extent to which students levels of satisfaction level of Strata-1 University of Bandar Lampung on the Sistem Informasi Akademik dan Administrasi Terpadu (SIATer) and any indicators that need to be improved in order to increase student satisfaction against SIATer. This type of research using a quantitative approach. The respondents determined using techniques research of Stratified Random Sampling with certain criteria. As for sample determination technique using tables Stephen Isaac & Willian B. Michael. From the results of the study showed that university students Bandar Lampung has yet fully satisfied against SIATer. Based on the method of End User Computing Statisfaction (EUCS), note that the indicators should be improved in order to increase student satisfaction is an indicator of formats, ease of use, and from the side of timeliness.